Aplicação de técnicas compensatórias na drenagem urbana, sob a ótica dos usuários do espaço: estudo de caso em São Carlos - SP - Almeida, Maria de Fátima (Universidade Federal de São Carlos, 2014)
Brazil, in the past decades, has experienced an accelerated urban growth. IBGE s (Brazilian Institute for Geography and Statistics) census data from 2010 showed that about 84% of Brazilian population lives in urban spaces. Tied to this growth, the classical system of urban drainage has proven itself to be insufficient and ineffective when it comes to flood control, water quality, the population´s quality of life and environmental sustainability. One alternative for this issue is the application of the low-impact development (LID) concept in the urban planning process through the Integrated Management Practices (IMPs), with the use of compensatory techniques in the management of urban pluvial water, seeking to compensate the alterations in the natural hydrological cycle caused by urbanization. Considering this context, this research has analyzed, under the perspective of public and private spaces users, the application of compensatory techniques (TCs) on urban drainage, considering legal, environmental, landscape, project, constructive, usage and space maintenance aspects. The research consisted of an application of a questionnaire to those users, according to the sample design of a case study, composed by two object areas, located in São Carlos (São Paulo State, Brazil), that use compensatory techniques on drainage. The Study Area I UFSCar, consists of a university campus, with the sample of 90 students, 19 employees and 40 professors; Study Area II, Montreal condominium, a residential space with the sample of 50 residents. The development of the questionnaires was based seeking to answer doubts and questions that arose during the process of implementation of compensatory techniques on UFSCar campus Study Area I, together with issues debated on Research Group G-Hidro. Results showed good acceptance of the existent legislation and, consequently, of the techniques, indicating that the lack of information is the main obstacle to their appliance. It is expected that the obtained results contribute to subsidize actions of straightening and enlargement of sustainable practices on urban drainage.
Keywords: Drenagem urbana; Técnicas compensatórias; Usuários; Urban drainage; Compensatory techniques; Users; ENGENHARIAS